Haplodeficiency of Cathepsin D does not affect cerebral amyloidosis and autophagy in APP/PS1 transgenic mice. Issue 2 (26th May 2017) - Cheng, Shaowu; Wani, Willayat Y.; Hottman, David A.; Jeong, Angela; Cao, Dongfeng; LeBlanc, Kyle J.; Saftig, Paul; Zhang, Jianhua; Li, Ling
Abstract: Autophagy and lysosomal function are important for protein homeostasis and their dysfunction have been associated with Alzheimer's disease (AD). Increased immunoreactivities of an important lysosomal protease, cathepsin D (Cat D), are evident in amyloid plaques and neurons in patients with AD. This study tests the hypothesis that deleting one allele of the cathepsin D gene (Ctsd) impacts cerebral β‐amyloidosis in amyloid‐β precursor protein (APP)sw/PS1dE9 (APP/PS1) double transgenic mice. Despite a significant 38% decrease in Cat D level in APP/PS1/ Ctsd +/− compared with APP/PS1/ Ctsd +/+ mice, no changes in steady state levels and deposition of Aβ were found in the brain. There were also no differences in APP processing, the levels of two other Aβ‐degrading proteases, the levels of autophagy related protein, such as LAMP2, P62, LC3‐I, LC3‐II, and Beclin‐1, or the markers of neuroinflammation, observed between the APP/PS1/ Ctsd +/+ and APP/PS1/ Ctsd +/− mice. Our findings demonstrate that in wild‐type mice, Cat D protein levels are either in excess or redundant with other factors in the brain, and at least one allele of Ctsd is dispensable for cerebral β‐amyloidosis and autophagy in APP/PS1 transgenic mice. Abstract : Previous studies in vitro have suggested that cathepsin D (Cat D) may play an important role in β‐amyloidosis and autophagy‐related processes in the brain. Using a mouse model in which one allele of the Cat D gene was deleted, we found that Cat D haplodeficiency had no impact on the level and deposition of amyloid‐β (Aβ) in the brain of APP/PS1 double transgenic mice, which co‐overexpress amyloid‐β precursor protein (APP) with the Swedish double mutation and presenilin 1 (PS1) with deletion of exon 9. We further showed that Cat D haplodeficiency did not affect APP processing, the levels of other Aβ‐degrading proteases such as insulin degrading enzyme and neprilysin, the levels of autophagy‐related proteins, or the markers of neuroinflammation. Our findings demonstrate that in wild‐type mice, cathepsin D protein levels are either in excess or redundant with other factors in the brain, and at least one allele of Cat D gene is dispensable for cerebral β‐amyloidosis and autophagy in APP/PS1 transgenic mice.